WHY NATIONS GO TO WAR/JOHN G. STOESSINGER - Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2011)
This 11th edition of Why nations go to war analyses ten case studies covering major international wars. The particular focus of each of the case studies turns upon the personalities of political and military leaders. Stoessinger emphasises that people go to war or precipitate wars. War is not some faceless entity that merely unfolds in some inexplicable way. In a critical stance towards attempts to explain war, the author holds that personalities often do not receive their due recognition in publications on war. Decisions by leaders to go to war or leadership decisions that result in warlike acts causing societies or vulnerable sections of society to suffer, receive attention in this updated edition of Why nations go to war. It is in the particular focus on people (the leaders who decide to go to war) where Stoessinger seeks for “… common truths about war in our time”.